Vesicles in fatty acid salt-fatty acid stabilized o/w emulsion - emulsion structure and rheology - Niraula, B.B.; Seng, T.N.; Misran, M. (2004)
Texture and rheology properties of fatty acid salt-fatty acid mixture stabilized oil-water (o/w) emulsions are being explored. While NaOH solution was introduced as aqueous phase, oil phase contained in it dissolved lauric acid. When these oil and water phases are brought in contact, a portion of lauric acid transforms into sodium laurate in situ via acid-base reaction, the combination of which at a certain threshold concentration and above is believed to act as emulsifier in stabilizing the given o/w emulsion system. Light microscopy under cross polarizing conditions suggested that in addition to the formation of surfactant stabilized emulsion droplets, formation of molecular aggregates of vesicle type is imminent in these conditions, both the size and number density of which is found to be a function of emulsifier concentration ratio. The concentration of emulsifier (sodium laurate-lauric acid) is being assessed in this work indirectly as a function of NaOH concentration, due to the problem associated with its quantification. Non or a very small number of vesicles was observed at NaOH concentration below 0.4M, whilst in the presence of 0.4-0.8M NaOH the vesicle population increased substantially. While vesicle population density decreased past 0.8M NaOH, their size increased with NaOH concentration from 0.8 to 1M. These observations suggested that sodium laurate-lauric acid concentration ratio that corresponds to 0.6-0.8M NaOH is the optimum NaOH concentration at which maximum vesicle number density is observed. As far as rheology properties are concerned, at any given Î³Ì, in the absence of NaOH, the Î· of the oil solubilized lauric acid was found to be much lower than the Î· of corresponding sodium laurate-lauric acid stabilized o/w emulsion. Though Î·(Î³Ì) profiles of sodium laurate-lauric acid stabilized o/w emulsion was not a linear function under the given sets of experimental conditions, at all conditions Î· strongly depended on sodium laurate-lauric acid concentrations (concentration of NaOH in this case). What more is that at any given Î³Ì, the Î· was observed to be maximum at sodium laurate-lauric acid concentration ratio that corresponded to 0.8M NaOH, a situation which corresponds to the presence of the maximum vesicle number density. In addition to Î·, in the presence of 0.8M NaOH, higher values of ÏY was observed, implying that at this particular NaOH concentration these emulsions possessed greater degree of emulsion structuring compared to other NaOH concentrations. These observations lead to the conclusion that sodium laurate concentration plays a great role in the formation of fatty acid salt vesicles, that under the given set of conditions sodium laurate-lauric acid concentration corresponding to 0.8M NaOH is the optimum concentration at which maximum number of vesicles are produced, and that rheology property of these emulsions depend not only on emulsion droplets but also on the vesicle number density and size. Test on oscillatory shear mode also suggested that much like o/w emulsions stabilized with other type surfactant, the viscoelastic properties of these sodium laurate-lauric acid stabilized o/w emulsions depended highly on surfactant concentration. The fact that Gâ³ response was dominant over Gâ² response at all measured frequency and sodium laurate-lauric acid concentration, it is evident that viscous property dominated over elastic property in these emulsion. The good news is that improved elastic property is observed at sodium laurate-lauric acid concentration that corresponded to 0.6-0.8M NaOH. And not only, in the presence of 0.8M NaOH, while Gâ³ response of these samples was dominant over Gâ² response at low domain, the dynamic moduli crossed-over at around 2Hz, past which the Gâ² response became dominant over Gâ³. This implies that, at this particular surfactant concentration, emulsions stabilized with sodium laurate-laurate mixture displays an excellent viscoelastic property pertaining to emulsions used in pharmaceutical and cosmetic products. This further suggests that in the presence of 0.8M NaOH these o/w emulsion both spread easily and stabilized better as well as possess long storage stability and shelf life. With these dynamic moduli responses it is not surprising that the Î´ of these sodium laurate-lauric acid stabilized emulsions decreased with NaOH concentration from 0.4 to 0.8M. The fact that these emulsion showed smallest Î´ in the presence of 0.8M NaOH as opposed to other NaOH concentrations, it is evident that solid-like elastic property of these emulsions is enhanced and improved at this NaOH concentration. As far as oil type is concerned mineral oil based systems showed better rheology properties compared to corresponding paraffin oil based systems.